Global Burden of Kidney Cancer Attributable to High Body Mass Index in Adults Aged 60 and Older from 1990 to 2021 and Projections to 2040: A Systematic Analysis for the Global Burden of Disease Study - Lin J; Zhang Z; Meng X; Yin X; Pu L; Xiang C; Yang J (Clinical Epidemiology, 2025)
Jiaquan Lin,1,* Zhichao Zhang,2,* Xiaorong Meng,3,* Xiaofei Yin,4 Lingling Pu,4 Chenhui Xiang,5 Jing Yang4 1Department of Radiology, CHINA MCC5 GROUP CORP. LTD. HOSPITAL, Chengdu, 610081, People’s Republic of China; 2Kangfu Kidney Hospital of Chengdu, Chengdu, 610047, People’s Republic of China; 3School of Clinical Medicine, Chengdu Medical College, Chengdu, 610500, People’s Republic of China; 4Demonstration Center for Experimental Teaching in Biomedicine, Chengdu Medical College, Chengdu, 610500, People’s Republic of China; 5Department of Urology, The First Affiliated Hospital of Chengdu Medical College, Chengdu, 610500, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chenhui Xiang; Email xiangch6617@my.com Jing Yang, Email jingyang@cmc.edu.cnBackground: With global aging, cancer burden rises. Kidney cancer is significantly influenced by high body mass index (BMI), especially in the elderly. This study analyzes the burden of kidney cancer attributable to high BMI in those aged ≥ 60, clarifying causes and future trends.Methods: Using Global Burden of Disease (GBD) 2021 study, we assessed kidney cancer burden due to high BMI in population aged ≥ 60 from 1990 to 2021, comparing deaths, disability-adjusted life years (DALYs), age-standardized rate (ASR) of DALYs (ASDR), and mortality (ASMR). Stratified by Socio-Demographic Index (SDI), region, sex, and age, we evaluated spatiotemporal trends and inequalities. Finally, the Bayesian Age-Period-Cohort (BAPC) model predicted burden changes through 2040.Results: From 1990 to 2021, DALYs and deaths from high BMI-induced kidney cancer in those aged ≥ 60 increased by 165.82% and 186.39%, driven by population growth. In 2021, ASDR was 45.55/100,000 and ASMR 2.39/100,000. Regional differences were significant. DALYs and deaths expanded, especially in those aged ≥ 95. Males had higher burden than females. SDI correlated positively with ASDR and ASMR (r> 0, P< 0.05). Health inequalities continue to rise. By 2040, burden is projected to rise, especially in low-middle and low SDI regions, more in males.Conclusion: This study shows a significant increase in kidney cancer burden due to high BMI in those aged ≥ 60 over 32 years, driven by population growth. Disparities across regions, genders, and age groups highlight the need for targeted prevention and early intervention, especially for high-risk groups (males, elderly, low-middle SDI regions), to reduce burden and optimize healthcare resource allocation.Keywords: kidney cancer, high BMI, elderly, SDI, gender differences, trend projection